1998
DOI: 10.1111/j.1467-8624.1998.tb06167.x
|View full text |Cite
|
Sign up to set email alerts
|

Similarities between Friends and Nonfriends in Middle Childhood

Abstract: Similarities were assessed between target children (mean age, 11.1 years) and their friends and nonfriends, respectively. One target child of each sex (N = 192), along with one same-sex friend and one nonfriend, were selected from 102 participating classrooms. "Guess who" nominations obtained within these classrooms were used to measure prosocial behavior, antisocial behavior, shyness / dependency, and sociometric status; selfreports were used to measure depressive symptoms. Children and their friends were mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
81
0
7

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(96 citation statements)
references
References 27 publications
6
81
0
7
Order By: Relevance
“…Thus, our hypothesis that aggressive children affiliate was confirmed. The findings correspond with studies among school‐age children, which showed that behaviorally similar children cluster together (Haselager et al, 1998; Pellegrini et al, 1999). This affiliation of aggressive children might lead to an increase in bullying behavior as they adapt their behavior to each other (Dishion, Patterson, & Griesler, 1994).…”
Section: Peer Relationships Of Bullies Bully‐victims and Victimssupporting
confidence: 90%
See 1 more Smart Citation
“…Thus, our hypothesis that aggressive children affiliate was confirmed. The findings correspond with studies among school‐age children, which showed that behaviorally similar children cluster together (Haselager et al, 1998; Pellegrini et al, 1999). This affiliation of aggressive children might lead to an increase in bullying behavior as they adapt their behavior to each other (Dishion, Patterson, & Griesler, 1994).…”
Section: Peer Relationships Of Bullies Bully‐victims and Victimssupporting
confidence: 90%
“…Cairns et al (1988) established that not all aggressive children lack friends. In fact, several studies have indicated that bullies, particularly boys, have large friendship networks (Boulton, 1999; Huttunen & Salmivalli, 1996); that aggressive children tend to affiliate (Cairns et al, 1988; Espelage, Holt, & Henkel, 2003; Haselager, Hartup, Lieshout, & Riksen‐Walraven, 1998; Pellegrini et al, 1999); and that highly aggressive boys can even be among the most popular and socially connected children (Rodkin, Farmer, Pearl, & Van Acker, 2000). These findings suggest that as bullies and bully‐victims are aggressive, they might cluster together.…”
mentioning
confidence: 99%
“…ex., Urberg, Degirmencioglu, & Tolson, 1998) -, com sujeitos do mesmo sexo -por ainda serem raras as nomeações ao sexo oposto, nesta fase do desenvolvimento (p. ex., Haselager, Hartup, van Lieshout, & Riksen-Walraven, 1998) -e, por questões metodológicas, com alguém da mesma turma. Contudo, seria interessante considerar um critério mais abrangente, que pudesse incluir as amizades com pares de sexo oposto e/ou de outros contextos, de modo a esclarecer, de forma inequívoca, se os indivíduos que foram tratados como não tendo amigos não os têm mesmo, ou não os têm apenas devido aos critérios definidos.…”
Section: Limitações E Direções Futurasunclassified
“…Sijtsema, Lindenberg, & Veenstra, 2010). Indeed, victims often have victimized friends (Haselager, Hartup, van Lieshout, & Riksen-Walraven, 1998;Hodges et al, 1997;Salmivalli, Huttunen, & Lagerspetz, 1997). However, it is not clear whether adolescents choose each other as friends based on pre-existing similarity in victimization (selection) or whether they become similar in being victimized over time (influence).…”
Section: Introductionmentioning
confidence: 99%